Efek xenia dan metaxenia pada persilangan tomat ranti dan tomat cherry - Natalia Indah Widyasmara; Florentina Kusmiyati; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Cherry tomato have various colour, shape and nutritious fruit. The aim of this research was to make population for genetic selection and to know about xenia and metaxenia effect on tomato crossing. The crossing was assigned in dialel crossing combination with Ranti tomato, Cherry tomato var. Grape, Red Pear and Indigo Rose as a crossing parents. The crossing combination was Ranti x Grape, Ranti x Red Pear, Ranti x Indigo Rose, Grape x Ranti, Grape x Red Pear, Grape x Indigo Rose, Indigo Rose x Grape, Indigo Rose x Ranti, Indigo Rose x Red Pear. Parameter measured were crossing ability, fruit set ability, fruit ripening age, seed number and fruit shape. The result showed that Grape x Red Pear crossing combination had the highest crossing ability and Indigo Rose x Red Pear had the highest fruit set ability. Xenia and metaxenia effects were showed in fruit ripening age, seed number and fruit shape. Genotype of Red Pear x Indigo Rose was found as superior genotype candidate for ripening age, seed number and had highest percentage of fruit shape alteration. Keywords : Hybridization, xenia, metaxenia, tomato, cherry tomato.